IMMUNOLOGICAL ASPECTS OF DESTABILIZATION OF CORONARY HEART DISEASE IN PATIENTS OF WORKING AGE - Khasanjanova F.O.; Adilova D.N; Khudoiberdiev A.A (Scholar Express Journals, 2024)
The study assessed the role of interleukins in the destabilization of coronary heart disease in patients of working age. The study included 72 male patients aged 20 to 69 years hospitalized in emergency departments No. 1 in the period from 2022 to 2023 on the basis of the Samarkand branch of the Republican stable angina Research and Practical center for emergency medically stable angina care. All patients underwent a general clinical examination (anamnesis collection, anthropometric and physical examination of the patient, measurement of blood pressure, heart rate). Laboratoryinestable angina pectoris examination included clinical blood tests, biochemical blood analysis, examination of hemostasis parameters, upon admission and in dynamics on the 2nd and 7th day of admission, ECG, echocardiography, lung radiography, ultrasound according to indications. Maximum levels of proinflammatory cytokines and low concentrations of IL–4 and IL–10 was detected in acute myocardial infarction. An important role in the progression of coronary heart disease and the formation of ACS belongs to the activation of immuno-inflammatory reactions.
Keywords: coronary heart disease; working age; ACUTE myocardial infarction